PERAN PENYULUH PERTANIAN TERHADAP PENGEMBANGAN KELOMPOK TANI DI NAGARI TANJUNG LOLO KECAMATAN TANJUNG GADANG - Nurazizah, Wahyuli; Hendrita, Vivi (LPPM Universitas Malikussaleh - Indonesia, 2024)
This research aims to determine the role of agricultural instructors in the development of farmer groups in Nagari Tanjung Lolo, Tanjung Gadang District, Sijunjung Regency in the Kami Saiyo Farmer Group. The research was carried out from January to September 2023. The sample in this research was determined purposively based on the class level and farmer group level. the most active compared to other farmer groups in the target area. The number of samples in this study was 25 people. The data used in this research is primary data and secondary data. Data analysis in this study used a Likert scale. The results of the research show that agricultural extension workers in Nagari Tanjung Lolo, Tanjung Gadang District, Sijunjung Regency are running well in terms of their performance. The extension workers play a very important role in developing farmer groups. This is indicated by obtaining a total score of 4.06 with the information that it plays a very important role. Meanwhile, the obstacle faced by extension workers is the low level of education of farmers which influences the farmers' mindset.